PENGARUH DUA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS KUBIS BUNGA PADA KEDALAMAN MUKA AIR TANAH YANG BERBEDA DENGAN SISTEM BUDIDAYA JENUH AIR DI LAHAN PASANG SURUT SULFAT MASAM - Suduy, Oswaldy; Nurjani, Nurjani; Basuni, Basuni (Fakultas Pertanian, Universitas Janabadra, 2024)
Cauliflower is a type of vegetable whose flower parts are used for consumption and has a high economic value. This research aims to obtain a better combination of manure and varieties for the growth and yield of cauliflower plants and to determine the effect of depth of groundwater level on the growth and yield of two varieties of cauliflower against two depths of groundwater level. This research was conducted in the tidal land of Golden River Camp Kalimas Tengah street, Mawar Hamlet, Kalimas Village, Sungai Kakap Sub-district, Kubu Raya Regency, West Kalimantan Province from July to November 2023. The design used in this research was a Split Block Design, which consisted of 2 factors repeated 3 times in each treatment. The first factor (main plot) is the depth of the water table (D) d1 = 20 cm, d2 = 30 cm and the second factor (sub plot) is the combination of manure and varieties (U) u1 = chicken manure + Larissa, u2 = goat manure + Larissa, u3 = chicken manure + Snow White, u4 = goat manure + Snow White. The observation variables observed in this study were the number of leaves, plant fresh weight, leaf area, plant dry weight, flower appearance, crop diameter and crop weight. Based on the results showed that chicken manure and goat manure are equally good for increasing the growth and yield of cauliflower on acid sulphate soil and the depth of the groundwater level of 30 cm was better for increasing the growth and yield of flower cabbage plants on acid sulphate soil.